Frequency of HER-2 over Expression in the Patients with Breast Cancer after Mastectomy - S kargar; B alavi farzane (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2013)
Introduction: HER-2 is a protein receptor of growth. Approximately 25% of breast cancers have overexpress HER-2. This study was designed to determine frequency of HER-2 overexpression in patients with breast cancer. Additionally, it intended to explore its relationship with some variables such as age, histopathologic diagnosis,tumor size, axillary lymph node involvement. Methods: This analytic cross-sectional study was conducted on patients with breast cancer whose breast tissue specimen was referred to pathology laboratory of Shahid Sadooghi hospital of Yazd during 1389 and 1390. Results: In our study, 147 patients were investigated who were all females with average age of 50.34 years with 13.3 years standard deviation. 54.5% of them were HER-2/neu positive and frequency of HER-2 was higher in patients with older age, larger size tumor, ductal carcinoma diagnosis and axillary lymph node involvement, though there wasn't any statistically significant difference between these variables and HER-2 overexpression. Conclusion: In our study, frequency of Her-2 overexpression was more than other studies and frequency of HER-2 was higher in patients with older age, larger size tumor, ductal carcinoma diagnosis and axillary lymph node involvement but there wasn't any statistically significant difference between these variables and HER-2 overexpression. Regarding high frequency of HER-2 overexpression in this study that can be duo to genetic and ethnic variations, we recommend that HER-2/neu screening test should be done in all patients with breast cancers specially those with ductal carcinoma diagnosis, larger size tumor and axillary lymph node involvement.